2008
DOI: 10.1002/ibd.20401
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tissue eosinophilia in the pouch and afferent limb in patients with restorative proctocolectomy

Abstract: Tissue eosinophilia in the pouch was more prominent than that in the afferent limb in patients with restorative proctocolectomy. Tissue eosinophilia in the pouch and afferent limb appeared to be associated with different risk factors. These findings suggest that luminal factors in different topographical locations of the pouch may contribute to eosinophil-mediated inflammation at these sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Schmidt et al [9] showed that terminal ileal eosinophils are significant predictors of active inflammation in subsequent IPAA pouch biopsy specimens, but lymphocyte aggregates and intraepithelial lymphocytes are not. Moreover, tissue eosinophilia in the pouch is reportedly more Dig Surg 2018;35:138-143 DOI: 10.1159/000477268 142 prominent than that in the afferent limb in patients who have undergone IPAA [37]. Although pouchitis seems to be associated with eosinophil-mediated inflammation based on the results of these studies, fewer eosinophils in the colon than in the ileum has a significant impact on the development of pouchitis and chronic pouchitis.…”
Section: Discussionmentioning
confidence: 56%
“…Schmidt et al [9] showed that terminal ileal eosinophils are significant predictors of active inflammation in subsequent IPAA pouch biopsy specimens, but lymphocyte aggregates and intraepithelial lymphocytes are not. Moreover, tissue eosinophilia in the pouch is reportedly more Dig Surg 2018;35:138-143 DOI: 10.1159/000477268 142 prominent than that in the afferent limb in patients who have undergone IPAA [37]. Although pouchitis seems to be associated with eosinophil-mediated inflammation based on the results of these studies, fewer eosinophils in the colon than in the ileum has a significant impact on the development of pouchitis and chronic pouchitis.…”
Section: Discussionmentioning
confidence: 56%
“…Biopsies from the pouch often show a variable increase in the number of intramucosal eosinophils. 6 Prominent eosinophils were observed in 44% of the involved biopsies 4 . Thus, a low threshold for utilizing CD117 stain to confirm the presence of subtle mast cell aggregates can be very helpful.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies, however, have reported a possible dual role for the eosinophil with noted involvement in tissue destruction and repair in the different stages of UC as eosinophils were actually higher in inactive UC than in the active phase of the disease [ 28 , 29 ]. Shen et al found that tissue eosinophilia in ileal pouch mucosa in IBD patients treated with restorative proctocolectomy was found to be more prominent than that in the afferent limb, suggesting that luminal factors in different areas of the bowel may contribute to eosinophil-mediated inflammation [ 30 ]. Our finding of eosinophilia in the rectosigmoid area of the patients later diagnosed with IBD in comparison to abdominal pain patients suggests that eosinophilia may be an early indicator of disease progression.…”
Section: Discussionmentioning
confidence: 99%